2022
DOI: 10.1007/s12559-022-10048-w
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Approach for Aggressive Political Discourse Analysis on Twitter

Abstract: Political tensions have grown throughout Europe since the beginning of the new century. The consecutive crises led to the rise of different social movements in several countries, in which the political status quo changed. These changes included an increment of the different tensions underlying politics, as has been reported after many other political and economical crises during the twentieth century. This article proposes the study of the political discourse, and its underlying tension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 70 publications
(42 reference statements)
0
5
0
2
Order By: Relevance
“…El análisis a través de plataformas sociales en línea (OSP), a pesar de excluir medios tradicionales y otros formatos (p. ej., programas electorales), es relevante, dado que sus usuarios más activos e influyentes son los periodistas, políticos y sus partidarios y, por tanto, Twitter es una plataforma relevante en la configuración de la agenda pública (Torregrosa et al, 2023).…”
Section: Vox Ppunclassified
“…El análisis a través de plataformas sociales en línea (OSP), a pesar de excluir medios tradicionales y otros formatos (p. ej., programas electorales), es relevante, dado que sus usuarios más activos e influyentes son los periodistas, políticos y sus partidarios y, por tanto, Twitter es una plataforma relevante en la configuración de la agenda pública (Torregrosa et al, 2023).…”
Section: Vox Ppunclassified
“…In contrast to generic sentiment analysis, stance detection aims to identify the public’s opinions in relation to a concrete target, such as different issues, topics, events, products, political candidates, etc. Torregrosa et al [ 53 ] study the political discourse on Twitter from a sentiment analysis and “campaign tone” perspective as applied to the 2021 Spanish local elections in the Autonomous Community of Madrid. The authors then perform an n-gram and hashtag analysis of the results in order to facilitate a qualitative analysis of the debate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that aggressive behavior is prevalent on Twitter (Kwak et al, 2010;Wu et al, 2011). Several studies have created annotated datasets of aggression in various languages, such as English (Kumar et al, 2018b,a;Bhattacharya et al, 2020;Kumar et al, 2020;Ali et al, 2023), Hindi (Kumar et al, 2018b,a;Bhattacharya et al, 2020;Kumar et al, 2020), Bengali (Bhattacharya et al, 2020;Kumar et al, 2020;Sharif and Hoque, 2022), Italian (Gattulli et al, 2022), Spanish (Torregrosa et al, 2022), Turkish (Balci and Salah, 2015), and Russian (Gordeev, 2016). These datasets were curated from social media platforms such as Facebook, Twitter, YouTube, and others.…”
Section: Aggression Detectionmentioning
confidence: 99%
“…The use of aggressive language on social media has been studied in various contexts. The various types of aggressive behaviors directed toward robots with AI enhancements has studied by Oravec (2023) Torregrosa et al (2022) found that ideologically extreme political parties tend to use more aggressive language. Pascual-Ferrá et al (2021) explored how aggressive language is used in the online discourse around wearing face masks during the COVID-19 pandemic.…”
Section: Aggression Behaviormentioning
confidence: 99%
See 1 more Smart Citation